2006
DOI: 10.1016/j.biombioe.2006.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Methods for size classification of wood chips

Abstract: Methods for size classification of wood chips were analysed in an international round robin using 13 conventional wood chip samples and two specially prepared standard samples, one from wood chips and one from hog fuel. The true size distribution of these two samples (according to length, width and height) had been determined stereometrically (reference method) using a digital calliper gauge and by weighing each of the about 7000 wood particles per sample. Five different horizontal and three rotary screening d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 5 publications
1
27
0
Order By: Relevance
“…The size for the wood fibers was determined using a calliper gauge. The share of the wood fibers constant fraction was determined using a sieving method, which is the most appropriate procedure for defining the consistency of a fraction [17,23]. Individual fractions were thus sieved through different sieves with different openings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The size for the wood fibers was determined using a calliper gauge. The share of the wood fibers constant fraction was determined using a sieving method, which is the most appropriate procedure for defining the consistency of a fraction [17,23]. Individual fractions were thus sieved through different sieves with different openings (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the result of this analysis is presented in size distribution curves, which are not based on the cumulative percentage mass, as it is for sieve analysis, but refer to the percentage of the total particle projection area (or particle number). Dynamic online image analysis systems are considered particularly interesting because they can sort the particle sizes according to more than just one size parameter [8]. Hartmann et al [8] suggested it would be useful to launch a standardization process in order to include the image analysis method to the scope of applicable standard laboratory principles for biofuels, too, so as to overcome the drawbacks of the screening methods.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic online image analysis systems are considered particularly interesting because they can sort the particle sizes according to more than just one size parameter [8]. Hartmann et al [8] suggested it would be useful to launch a standardization process in order to include the image analysis method to the scope of applicable standard laboratory principles for biofuels, too, so as to overcome the drawbacks of the screening methods. Following this suggestion, the aim of this study is to analyze how image analysis combined with multivariate modeling methods can be used to construct cumulative size distribution curves based on chip mass (or weight), which can be compared with the sieving results required by EN standards.…”
Section: Introductionmentioning
confidence: 99%
“…On average, reproducibility is better for horizontal screenings than for rotary screening. However, if different measuring principles are applied, particle size analysis of biofuels is associated with high measuring uncertainties (Hartmann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On average, reproducibility is better for horizontal screenings than for rotary screening. However, if different measuring principles are applied, particle size analysis of biofuels is associated with high measuring uncertainties (Hartmann et al, 2006).Since the chip form (shape and size) influences the sieve results, the image analysis could provide a method which is sensitive to the geometrical shape for determining a more accurate measure of size integrated with shape (Fernlund, 1998).Consiglio per la Ricerca e la sperimentazione in Agricoltura, Unità di ricerca per l'ingegneria agraria (CRA-ING) is conducting a research activity for developing a new method, based on the image analysis, for the classification of wood particles, depending on both size and shape. …”
mentioning
confidence: 99%